Planning Management: Bunton Village Owned Enterprises (BUMDES) Adipala District Cilacap District - Elok Ainur Latif; Mutia Pamikatsih; Rahmat AlHakim (Jurnal Ilmu Sosial Mamangan, 2023)
BUMDes is one method that can be utilized by villages in managing the potential or economic activities produced by their villages. Bunton is one of the villages in Adipala District, Cilacap Regency which also has an active BUMDes in its activities. The aim of this research is to determine management patterns, especially regarding the planning function implemented by BUMDes in Bunton Village. The reason for choosing BUMDes in this village is because based on initial observations from research, it shows that Bunton Village has BUMDes income which tends to increase every year compared to other villages in the same sub-district. The income received by BUMDes Bunton comes from the permanent business units which it successfully manages. Through this research, it is hoped that the management planning pattern implemented by BUMDes in Bunton Village can become a model BUMDes or inspiration for surrounding BUMDes so that together they are able to optimize the village's potential. In this way, the income received by each other BUMDes can also increase. By increasing BUMDes income, it is hoped that the economic welfare of local residents can also increase. The method used in this research uses a qualitative approach with the analysis techniques used are observation, documentation and interviews with related parties. The research results show that management planning in BUMDes Bunton is very interesting. Apart from the fact that BUMDes optimizes tourism business units in its management, BUMDes can also carefully see big opportunities by collaborating with PLTUs which are still in the same village as BUMDes itself. BUMDes collaboration with PLTU is through procurement of goods and services provided by BUMDes to PLTU and participating in various projects run by PLTU. This means that as long as the PLTU is still operating in the area, BUMDEs Bunton will also still benefit from this collaboration .